Life-cycle crack resistance and micro characteristics of internally cured concrete with superabsorbent polymers. (30th October 2020) - Lyu, Zhenghua; Shen, Aiqin; Mo, Shixiu; Chen, Zhihui; He, Ziming; Li, Desheng; Qin, Xiao
Highlights: The effect of internal curing on crack characteristics at different ages is investigated. The internal curing parameters for life-cycle crack resistance is optimized by efficacy coefficient method. The micro characteristics of internally cured pavement concrete is studied. SAP could greatly improve the crack resistance of concrete in life cycle. Abstract: To explore the crack resistance of internally cured concrete with superabsorbent polymers (SAPs) during its life cycle, plate induction test at the early plastic stage, ring restraint test at the curing stage and three-point fracture test at the service stage were designed to systematically track the variations in the crack characteristics. The key internal curing parameters of the SAP mesh and extra water input are optimized by the weighted efficacy coefficient method. Internal curing with SAPs is demonstrated to postpone the cracking initiation time, limit the cracking potential and improve the fracture energy. XRD shows that the addition of SAPs does not change the type of hydration products but influences the intensity of the diffraction peaks. A larger particle size of SAPs results in a higher CH and lower peak intensity of β-C2S. It is indicated that SAPs can prolong the water release cycle and regulate the hydration process to ensure the continuous and uniform hydration of cementitious materials. The porosity and the critical pore diameters decrease with the continuing age of the concrete, indicating that SAPs effectively reduce the pore connectivity and improve the pore structure. The enhancement mechanism of internal curing was revealed with a narrower ITZ width and lower Ca/Si ratio, which reflect the improvement of the crack resistance of the concrete. The experimental procedure is useful for the evaluation of crack resistance during the life cycle of concrete and the popularization of engineering applications for internally cured concrete pavement.